2010
DOI: 10.1103/physrevb.82.174303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced acousto-optic interactions in a one-dimensional phoxonic cavity

Abstract: International audienceWe report on the occurrence of strong nonlinear acousto-optic interactions in a one-dimensional model phoxonic cavity that supports, simultaneously, photonic and phononic localized resonant modes, by means of rigorous electrodynamic and elastodynamic calculations. We show that these interactions can take place when photons and phonons of long lifetime are confined in the same region of space and lead to enhanced modulation of light by acoustic waves through multiphonon exchange mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
80
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…A main objective is the modulation of light by acoustic waves when both excitations are confined inside the same cavity or propagate with a slow velocity inside a waveguide. This topic has been intensively investigated in one-dimensional (1D) multilayer structures 10,11 before being extended to 2D and more recently to slab and strip structures.…”
Section: Introductionmentioning
confidence: 99%
“…A main objective is the modulation of light by acoustic waves when both excitations are confined inside the same cavity or propagate with a slow velocity inside a waveguide. This topic has been intensively investigated in one-dimensional (1D) multilayer structures 10,11 before being extended to 2D and more recently to slab and strip structures.…”
Section: Introductionmentioning
confidence: 99%
“…Eichenfield et al [23] experimentally demonstrated a one-dimensional (1D) optomechanical crystal (OMC) nanobeam cavity with large OM coupling. Psarobas et al [24] reported that a strong AO interaction occurs when acoustic and optical resonant modes are simultaneously confined in a 1D PXC cavity to motivate multi-phonon exchange. Gomis-Bresco et al [25] demonstrated a 1D PXC nanobeam cavity capable of transducing confined phononic modes inside a complete PNBG.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been realized that the same periodic patterning can simultaneously be used to modify the propagation of light and acoustic waves of similar wavelength [9,10]. Such phoxonic or optomechanical crystals can be engineered to yield strong optoacoustic interactions due to the colocalization of optical and acoustic fields [11][12][13][14].…”
mentioning
confidence: 99%
“…It has also been realized that the same periodic patterning can simultaneously be used to modify the propagation of light and acoustic waves of similar wavelength [9,10]. Such phoxonic or optomechanical crystals can be engineered to yield strong optoacoustic interactions due to the colocalization of optical and acoustic fields [11][12][13][14].Utilizing silicon-on-insulator (SOI) wafers, similar to that employed to form planar photonic crystal devices [6], patterned silicon nanobeam structures have recently been created in which strong driven interactions are manifest between localized photons in the λ ¼ 1500 nm telecom band and GHz-frequency acoustic modes [13,15,16]. These quasi-one-dimensional (1D) optomechanical crystal (OMC) devices have led to new optomechanical effects, such as the demonstration of slow light and electromagnetically induced amplification [15], radiation pressure cooling of mechanical motion to its quantum ground state [16], and coherent optical wavelength conversion [17].…”
mentioning
confidence: 99%